Integrated Pest Management and Pest Control Current and Future Tactics - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2012)
Integrated Pest Management is an effective and environmentally sensitive approach that relies on a combination of common-sense practices. Its programs use current and comprehensive information on the life cycles of pests and their interactions with the environment. This information, in combination with available pest control methods, is used to manage pest damage by the most economical means and with the least possible hazard to people, property, and the environment.